Proceedings of the ACL-IJCNLP 2009 Conference Short Papers on - ACL-IJCNLP '09 2009
DOI: 10.3115/1667583.1667589
|View full text |Cite
|
Sign up to set email alerts
|

Using syntax to disambiguate explicit discourse connectives in text

Abstract: Discourse connectives are words or phrases such as once, since, and on the contrary that explicitly signal the presence of a discourse relation. There are two types of ambiguity that need to be resolved during discourse processing. First, a word can be ambiguous between discourse or non-discourse usage. For example, once can be either a temporal discourse connective or a simply a word meaning "formerly". Secondly, some connectives are ambiguous in terms of the relation they mark. For example since can serve as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(159 citation statements)
references
References 8 publications
6
152
0
Order By: Relevance
“…Explicit connective classification is usually done beforehand. (Pitler and Nenkova, 2009) achieved an F-Score of 94.19% which was extended by (Lin et al, 2014) to get an F-score of 95.36%. Various approaches have been used for argument span labelling.…”
Section: Related Workmentioning
confidence: 99%
“…Explicit connective classification is usually done beforehand. (Pitler and Nenkova, 2009) achieved an F-Score of 94.19% which was extended by (Lin et al, 2014) to get an F-score of 95.36%. Various approaches have been used for argument span labelling.…”
Section: Related Workmentioning
confidence: 99%
“…Then every connective candidate is Figure 1: Framework of our end-to-end shallow discourse parser checked whether it functions as a discourse connective. Pitler and Nenkova (2009) showed that syntactic features extracted from constituent parse trees are very useful in disambiguating discourse connectives. Followed their work, Lin et al (2014) found that a connective's context and part-ofspeech (POS) are also helpful.…”
Section: Connective Identificationmentioning
confidence: 99%
“…Although the same connective may carry different semantics under different contexts, only a few connectives are ambiguous (Pitler and Nenkova, 2009). Following the work of Lin et al (2014), we introduce three features to train a sense classifier: the connective itself, its POS and the previous word of the connective.…”
Section: Explicit Sense Classificationmentioning
confidence: 99%
See 2 more Smart Citations